Why Do People Adopt Mobile Passports? An Extension of Technology Acceptance Model - Yoserizal, Yoserizal; Tovalini, Krismena; Hanoselina, Yulia (Jurnal Ilmu Administrasi Negara (JUAN), 2025)
The increasing demand for efficient public services in the immigration sector has driven the Directorate General of Immigration of Indonesia to innovate through the Mobile Passport (M-Passport) application. This digital platform enables the public to apply for new passports and renew expired ones online, aligning with national e-government policies to enhance service quality and operational efficiency. This study aims to examine factors influencing the adoption of M-Passport using an extended Technology Acceptance Model (TAM) by incorporating the variable of individual attractiveness. Specifically, it investigates the effects of individual attractiveness, perceived usefulness, and perceived ease of use on attitude, as well as their indirect influence on behavioral intention. A quantitative approach was applied, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) on data from 400 respondents who accessed M-Passport services at the Class I TPI Immigration Office in Padang. Non-probability convenience sampling was employed, and data were analyzed for validity, reliability, and hypothesis testing. Results reveal that three of six hypotheses were supported: individual attractiveness positively and significantly affects perceived usefulness; perceived ease of use positively and significantly affects perceived usefulness; and attitude positively and significantly affects behavioral intention. Conversely, individual attractiveness, perceived usefulness, and perceived ease of use showed no significant direct effects on attitude. The findings underscore the importance of enhancing the application’s visual appeal and ease of use to improve perceived usefulness and ultimately drive adoption. This research contributes both theoretically, by extending TAM in the context of public service innovation, and practically, by offering recommendations to immigration authorities for improving M-Passport uptake.